THE RIGHT TO ONE'S IMAGE, AS A RIGHT OF THE HUMAN PERSONALITY JURISPRUDENCE: Received: 17th October 2023; Revised: 25th October 2023, 07th November 2023; Accepted: 19th December 2023 - Todica, Carmen (PEOPLE: International Journal of Social Sciences, 2024)
Through a theoretical and practical approach, the study presents the main regulations of the right to image, as a personal non-patrimonial right: the Romanian Civil Code, the Romanian Constitution, and the new legislation in the field of personal data. The study presents practical issues such as jurisprudential solutions in Romania regarding the violation of the right to image in the online environment (Facebook, Instagram), television shows, and press articles. Also, the study deals with the much-disputed issues of using the person's image in the procedures for sanctioning the employees, analyzing how the National Authority for Supervision of Personal Data Processing (N.A.S.P.D.P.) from Romania sanctioned the abuses of the employers. The case studies and the analysis of European and Romanian legislation are also useful to students, theoreticians, and legal practitioners.